ANALISIS BUDIDAYA PEMBESARAN IKAN BARONANG (SIGANUS SP) DI KABUPATEN BURU: (Analysis of Baronang Fish (Siganus Sp) Enlargement Cultivation in Buru District) - Talakua, Matheos; Umagapi, Hesti; Masiri, Melani (Uniqbu Journal of Exact Sciences, 2023)
This study aims to find out whether or not the cultivation of the enlarged Bearfish (Siganus sp) is feasible or not. in Namlea Village, Namlea District, Buru Regency. This research was conducted for one month, from May to July 2022. From the results of the research by the three respondents of Baronang Fish (Siganus sp) cultivators in Floating Net Cages (KJA) in Namlea Village, Namlea District, Buru Regency it is very feasible to develop, because the income generated obtained every year the amount is very large. Based on an analysis of the Baronang Fish Cultivation Business (Siganus sp) using the Floating Net Cages (KJA) method in Namlea Village, Namlea District, Buru Regency, it can be concluded as follows: 1) Respondent 1 (first) KJA business requires improvement in technical terms of fish handling and maintenance as well as additions related to business management, and 2) Respondents 2 and 3's KJA business is feasible for development.